2023
DOI: 10.1002/adfm.202300169
|View full text |Cite
|
Sign up to set email alerts
|

Vertical‐type 3D/Quasi‐2D n‐p Heterojunction Perovskite Photodetector

Abstract: This research demonstrates a state‐of‐the‐art vertical‐transport photodetector with an n‐type 3D MAPbI3/p‐type quasi‐2D (Q‐2D) BA2MA2Pb3I10 perovskite heterojunction. This structure introduces a ≈0.6 V built‐in electric field at the n‐p junction that greatly improves the characteristics of the perovskite photodetector, and the presence of Q‐2D perovskite on the surface improves the life. The electrical polarities of the 3D and the Q‐2D perovskite layers are simply controlled by self‐constituent doping, making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…Vertical-structured PPDs, typically prepared in controlled environments such as glove boxes, have showcased promising performance in recent studies. 35–38 For instance, Hsiao et al integrated a quasi-2D perovskite layer into PPDs, forming a 3D/2D perovskite heterojunction, resulting in a low dark current density of 6.2 × 10 –10 A cm −2 and a high detectivity of 2.82 × 10 13 Jones. 35 Nevertheless, limited studies have been conducted on air-processed PPDs with vertical structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical-structured PPDs, typically prepared in controlled environments such as glove boxes, have showcased promising performance in recent studies. 35–38 For instance, Hsiao et al integrated a quasi-2D perovskite layer into PPDs, forming a 3D/2D perovskite heterojunction, resulting in a low dark current density of 6.2 × 10 –10 A cm −2 and a high detectivity of 2.82 × 10 13 Jones. 35 Nevertheless, limited studies have been conducted on air-processed PPDs with vertical structures.…”
Section: Introductionmentioning
confidence: 99%
“…35–38 For instance, Hsiao et al integrated a quasi-2D perovskite layer into PPDs, forming a 3D/2D perovskite heterojunction, resulting in a low dark current density of 6.2 × 10 –10 A cm −2 and a high detectivity of 2.82 × 10 13 Jones. 35 Nevertheless, limited studies have been conducted on air-processed PPDs with vertical structures. 39–41 Tang et al tried to manage the nucleation/growth of perovskites in the air by introducing low-polarity tert -butanol as an antisolvent, 39 achieving a PPD with a high responsivity of 1.93 A W −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D (including pure 2D and quasi-2D) perovskite modifications of 3D perovskite have attracted intense interest because the 2D layer plays a crucial role not only in passivating defects but also in boosting carrier extraction and improving moisture resistance. Yin et al revealed that the surface iodine-vacancy-induced trap states of 3D perovskite were reduced by 2D perovskite passivation, further decreasing the dark current density of PDs based on the Shockley–Read–Hall (SRH) mechanisms . Hsiao et al introduced a ∼0.6 V built-in electric field at the 2D/3D junction by establishing a vertical-type PD with an n-type 3D/p-type 2D heterojunction, yielding an external quantum efficiency (EQE) of 77.9% …”
Section: Introductionmentioning
confidence: 99%
“…Organic metal halide perovskites exhibit excellent optoelectronic properties, including high light absorption coefficients and carrier mobility. These properties make them suitable for applications in fields such as solar cells [ 5 , 6 , 7 ], photodetectors [ 8 ], and light-emitting diodes [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. While metal halide perovskites typically have a 3D structure [ 16 ], they can also form 2D layered structures known as Ruddlesden–Popper phases [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%